EFEKTIVITAS LAYANAN KONSELING KELOMPOK MENGGUNAKAN KEJENUHAN BELAJAR - muhammad irham fazlurrahman (Jurnal Psikoedukasia, 2023)
This research is motivated by the high level of learning saturation in students, this can be seen from the results of observations made at SMA Negeri 1 Grobogan, Grobogan Regency. This research uses a one group pretest posttest design which aims to find out how effective group counseling services are using relaxation techniques to reduce learning boredom for class XII students at SMA Negeri 1 Grobogan. The population is 228 students with a sampling technique that is purposive sampling technique, the selected sample is 8 students. The data collection method uses SPSS V.20. The test used in this study is a parametric test, namely the paired sample test. The purpose of this test is to measure the difference in pretest and posttest scores on students' learning saturation before and after being given treatment. The results of this research show that group counseling using relaxation techniques is effective in reducing learning saturation in students, this is evidenced from the results of the paired sample t-test with a probability value of sig. (2-tailed) 0.001<0.05. As well as with the difference in the average score of the learning saturation questionnaire 27.75% from the results of the pretest and posttest. This proves that group counseling using relaxation techniques can reduce learning boredom in students Keywords: (group counseling, relaxation technique, study boredom)